Analysis of Animal Husbandary information in the farm feature pages of leading Malayalam Dailies - Sathumadhavan T P (Department of Extension, College of Veterinary and Animal Sciences, 2000)
Study was a content analysis of animal husbandry information in farm . feature pages of four Malayalam dailies, namely Malayala Manorama, Mathrubhoorni,. Desabhimani and Deepika, for the period January to December 1999. Variables studied were space provided to different categories of animal husbandry news, modes of presentation, frequency of occurrence of news, seasonality, readability, relevancy and accuracy. Research findings revealed that the studied dailies provided less than one fourth space of farm feature pages for publishing animal husbandry information. Large animal category got more than 50 per cent coverage with three-fourth space occupied by articles on cows. Poultry articles occupied one-fourth space of animal husbandry information of farm feature pages. Where as small animals and pet animals occupied 17 per cent and seven per cent space respectively. News articles occupied maximum column length in all dailies studied. Frequency of occurrence of news articles, illustrations and question answers were found to be more when compared to other modes of presentation. Seasonality studies r.evealed that more than half the number of dairy articles and one eighth of poultry articles were seasonal. Average readability of dairy articles according to Fog index was 5.45 with more reading easiness. More than 50 per cent of dairy articles were found to be relevant. Just above two-third of scientific messages of dairy articles were accurate, whereas accuracy of general articles were found to be nearly 50 per cent.